Pemanfaatan Media Sosial Instagram Pada Acara The 8th Indonesia International Geothermal Convention and Exhibition 2022 Oleh PT Energi Kreatif Dinamika - Annisa Salsabila Nurcahyani; Heri Setyawan (Bisnis Event, 2023)
The management of Instagram social media is very important at this moment because through proper management, it can create a good and attractive company image. The need for innovation and creativity in managing social media is very high so that the public can easily access or find out about the company or a particular event. This writing aims to know and study the process of managing Instagram social media for an event. Using a qualitative descriptive research method, namely by collecting data results obtained during the Field Work Practice at PT Energi Kreatif Dinamika. The results of the study showed that the management of Instagram social media goes through 3 stages such as Editorial Plan, Content Plan, and Content Approval.